Eksistensi Tarian Kuda Lumping Marka Tilaras di Daerah Transmigrasi Desa Tirtamartani Kecamatan Buke Kabupaten Konawe Selatan - Wulandari, Sevi; Ashmarita, Ashmarita (JURNAL KABANTI: Kerabat Antropologi, 2024)
The aim of this research is to find out and describe the Marka Tilaras Lumping Horse Dance that has survived to this day and has become one of the most popular lumping horses in South Konawe Regency and to find out the efforts made by the Marka Tilaras Lumping Horse in Tirtamartani Village so that it can develop well. .The informants in this research gathered ten people, with the criteria for the informants selected being the head of Tirtamartani village, the chief executive, members of Kuda Lumping Marka Tilras, spectators of Kuda Lumping Marka Tilaras, and sellers of various snacks around the Kuda Lumping Marka Tilaras performance. Data collection in this research was direct research using field research techniques and observation techniques, as well as in-depth interviews. The results of the research show that the Kuda Lumping Marka Tilaras dance in Tirtamartani Village, Buke District, South Konawe Regency can survive to this day because it is to preserve culture, to develop the artistic talent and creativity of people who want to participate, and then to develop public awareness of the importance of cultural values.